The digital economy as a fundamental foundation intensive development of post-industrial society - Beisembai , Ye. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the modern theoretical and methodological foundations of the formation and development of the digital economy in the context of the transition of global production and economic processes to the post-industrial stage of evolution. Particular attention is paid to the scientific structuring of the concepts of traditional and digital economies, classification areas and types of the digital economy, the positive aspects of the influence of the digital economy on the general macroeconomic situation, taking into account its evolutionary stages, and the criteria for distinguishing the digital economy from the analogue one. In order to develop the organizational stages of the transition of the economy to a digital format, the sectors of the economy are designated that act as the foundation for the digitalization of all subsystems of socio-economic and industrial spheres. As a result, a methodology has been developed for transforming the economy from a traditional type to a digital one on an object and subject basis. As objects of digitalization, public and private organizations, as well as organizations operating in the format of public-private partnerships, were designated. As the subject of digitalization, research and development, technology transfer are indicated. At the same time, the calculation and economic methods for assessing investments in the digitalization of the economy are presented. The conducted studies are applied in nature and can be widely used in practice within the framework of the implementation of the State program «Digital Kazakhstan». The main research methods used were a systematic approach, analysis and synthesis, observation, and hypotheses.